Complexos do tipo cis-[Ru(L-phen)2(apy)2]2+ com interesse no tratamento de Mal de Alzheimer: propriedades físico-químicas e estudos de inibição da Acetilcolina Esterase - Chinini, Guilherme Luiz (Universidade Federal de São Carlos, 2011)
The photochemical and photophysical properties of the cis-[Ru(phen)2(4apy)2]2+ complex where 4apy= 4-aminopyridine are reported. In this work the complexes are thermically stable throughout the course of many hours in non-aqueous and aqueous solution and highly colored (red solution in the most of solvents). The absorption is characterized by two broad shoulders and an intense emission is found at 640 nm. Upon photolysis in aqueous solution, accompanied by spectroscopic techniques (UVvis, luminescence, 1H NMR, HPLC) cis-[Ru(phen)2(4apy)2]2+ complex loses the 4apy ligand to give the aquo complexes: cis-[Ru(phen)2(4apy)(H2O)]2+, cis- [Ru(phen)2(H2O)2]2+ and trans-[Ru(phen)2(H2O)2]2+. The aquo complexes have been synthesized and characterized using 1H NMR, FTIR and UV-vis spectroscopy. The photochemical mechanism is confirmed by TD-DFT calculations. Considering the role of acetylcholinesterase inhibitors in the Alzheimer disease treatments, the prepared complexes were tested for AChE inhibition using the Ellman and fluorimetric methods. In these studies Tacrine (hydrochloride-1,2,3,4-tetrahydroacridin-9-amine) was used for comparison purposes. The complexes were also evaluated for their toxicity towards to 3T3 and NG97 cells. The cis-complex binds with micromolar affinity to AChE and display an IC50 of 1.38. The cis-complex is a reversible competitive inhibitor while Tacrine gives mixed and uncompetitive inhibition with acetylcholine as the substrate. Citotoxicity studies showed that the cis complex presents a higher citoxicity against NG97 cells (IC50= 39.84 μmol.mL-1) and a lower citotoxicity toward 3T3 cell. We evaluated the in situ emissive activity of the complex cis-[Ru(phen)2(4apy)2]2+ through confocal microscopy, obtaining the expected contrast as well as the emissive loss resulting from the photolysis process. Overall, these results are of particular interest for designing intelligent metallodrugs based on photochemical and photophysical processes and offer promising potentials for the treatment of Alzheimer diseases.
Cis-[Ru(L-phen)2(apy)2]2+ complexes, with interest in the treatment of alzheimer‟s disease: physicochemical properties and acetylcholinesterase enzyme inhibition
Keywords: Química inorgânica; Complexos de rutênio; Química bioinorgânica; CIENCIAS EXATAS E DA TERRA::QUIMICA